Supply, fabricating and installation of the metal doors, louvers and grilles for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Retail Scape Limited to supply, fabricating and installation of the metal doors, louvers and grilles for the Brac University new campus project.